Re-designed flipped learning model in an academic course: The role of co-creation and co-regulation. (December 2017) - Blau, Ina; Shamir-Inbal, Tamar
Abstract: In traditional flipped classroom (FC), learning of new content mostly occurs through watching videos and transferring information from instructor to students utilizing technological tools. The present study devised and examined a novel extension of the FC model. This model adds components that acknowledge the roles of instructor, learners, peer assessment, and embedded evaluation. Moreover, it highlights the value of technology and digital tools in supporting and enhancing active individual and collaborative learning, and the development of self-regulated strategies in in-class and out-of-class settings. The model was investigated in a qualitative study, which was conducted in a blended academic course, including synchronous and asynchronous lessons. The participants were 36 graduate students who were studying towards a Master Degree in Education. The paper analyzed learning experiences and their interpretations by the students. In contrast to traditional FC model, the findings revealed active learning of students in both in- and out-of-class settings that took place before, during, and after the lesson. The instructor promoted extensive independent learning, learning regulation, continuous dialogue and collaborative interactions among peers. The re-designed model highlights co-creation of the course content and of digital learning outcomes by students, self-regulation and teamwork co-regulation, which are rare in higher education. Highlights: This paper analyses flipped learning experiences of graduate students. The findings suggests re-design of the flipped classroom model. Co-creation of content and learning outcomes by students are highlighted. Self-regulation was combined with co-regulation in virtual teams. The added value of technologies was reported both in- and out-of-class.